Intraoperative Real-time Cochlear Response Telemetry Predicts Hearing Preservation in Cochlear Implantation. Issue 4 (April 2016) - Campbell, Luke; Kaicer, Arielle; Sly, David; Iseli, Claire; Wei, Benjamin; Briggs, Robert; O'Leary, Stephen
Abstract : Aim: To monitor cochlear function during cochlear implantation and determine correlations with postoperative acoustic hearing. Background: Cochlear response telemetry measures cochlear function directly from cochlear implant electrodes. We have adapted this system to provide real-time cochlear response telemetry (RT-CRT) monitoring of a patient's acoustic hearing as the cochlear implant electrode array is inserted. Methods: Eighteen subjects (1 child and 17 adults) with sloping high frequency hearing loss were implanted with Cochlear Ltd slim straight arrays (CI422/CI522). Tone bursts (500 Hz, 100–110 dB) were presented at 14 Hz continuously during the array insertion. RT-CRT amplitudes were correlated with surgical manoeuvres recorded on the video from the operating microscope and with postoperative pure tone audiograms. Results: Despite an excellent overall rate of complete or partial hearing preservation (79%), RT-CRT identified that in 47% of these implantations there was transient or permanent reduction in the amplitude of the cochlear microphonic (CM). Patients with a preserved CM at the end of insertion had on average 15 dB better low-frequency hearing preservation. The CM amplitude was most vulnerable during the last few millimeters of insertion or when inadvertent movement of the array occurred after full insertion. Physical contact/elevation of the basilar membrane is hypothesized as a likely mechanism of hearing loss rather than overt physical trauma. Conclusion: RT-CRT can be used to predict early postoperative hearing loss and to potentially refine surgical technique. In the future, feedback of RT-CRT may prove to be a valuable tool for maximizing preservation of residual hearing or providing feedback on electrode contact with the basilar membrane.